PENGARUH SHOLAT DHUHA TERHADAP PEMBENTUKAN KARAKTER SISWA KELAS II DI MIS AR-ROYYAN SIDORUKUN KEC. PANGKATAN KAB. LABUHANBATU 2023/2024 - Kana Dewi Azlini; Galih Orlando; Yuli Yani (Cendekia Madani Nusantara, 2025)
The main issue in this research is whether the use of dhuha prayer affects the character of second-grade students at MIS Ar-Royyan Sidorukun, Pangkatan District, for the 2023/2024 academic year. This research aims to determine the character of the students. In this lesson, the Dhuha prayer among second-grade students of MIS Ar-Royyan Sidorukun, Pangkatan District. This research is a quantitative study conducted in two cycles with the research subjects being 32 second-grade students. Observation data collection technique. The research results showed that the character of students performing dhuha prayer was 25.93%. Then, the results of the dhuha prayer and the character of students who are actively engaged in classical activities are 84.07%. This proves that further action is not necessary. Therefore, by using the dhuha prayer, it has been proven to be able to shape the character of second-grade students at MIS Ar-Royyan Sidorukun, Pangkatan District, for the 2023/2024 academic year